Compliance with standard precautions, sharp injuries, and blood and body fluid exposure among healthcare workers - Shadi Moshksar; Mohammad Mehdi Nabavi; Mina Danaei; Mohsen Momeni; Mehrdad Askarian (Tehran University of Medical Sciences, 2023)
Background & Aim: Healthcare workers are exposed to certain infectious diseases through needlestick injuries and exposure to blood and other bodily fluids. This study aimed to determine the prevalence of needlestick injuries and blood and other body fluids exposure among healthcare workers at Namazi Hospital in Shiraz, Iran. Methods & Materials: This cross-sectional study was conducted on 656 Healthcare workers, including students and staff in medical, nursing, laboratory, service, and operating room groups, at the Namazi Hospital, in 2019. A questionnaire with four parts, including demographics, questions about using sharps containers, needle recapping, masks, and glasses, and the experience of sharps injuries or blood and body fluid exposure and reporting them, was distributed using the quota sampling method. To analyze the results, the T‑test and Chi-square test were performed. Results: Nearly 75.2% of the participants always used sharps containers, and 21.7% never recapped syringes. Sharps injuries and blood and body fluid exposure occurred in 40.7% and 39.8% of the participants. Occupation (P<0.001), being a student (P: 0.048), and age (P: 0.008) were associated with sharp injuries. Occupation (P: 0.001), gender (P: 0.016), and age (P<0.001) differed in exposed and no exposed participants to blood and body fluids. The prevalence of reporting exposure was not significantly different between men and women, occupation groups, students and staff, and different ages (P> 0.05). Conclusion: Hospital managers should provide effective educational interventions to protect against occupational hazard exposures. Also, they should provide protective equipment for Healthcare workers.